DAMPAK ISU ISLAMOFOBIA VIRAL TERHADAP PERSEPSI PERADABAN ISLAM DI MEDIA SOSIAL - Melani Indriawati; Raihan Naufal Rahman; Rafah Parhatusshafwah (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the impact of viral Islamophobia issues on social media on perceptions of Islamic civilization. Social media has become a key platform for spreading negative narratives about Islam, influencing global public opinion. This research employs a literature review approach, drawing on books, academic journals, and relevant articles. The findings reveal that Islamophobia on social media reinforces negative stereotypes against Muslims, triggers discrimination, and poses challenges for Islamic propagation in the digital age. However, social media can also be utilized to counter negative narratives through digital literacy education, the production of positive content, and collaboration with social media platforms. This study highlights the importance of active roles by Muslim communities and religious leaders in promoting the peaceful and inclusive values of Islam. Effective strategies are essential to foster positive perceptions of Islam and support social harmony amidst the challenges of the digital era.